(untitled) (Research, Society and Development, 2022)
Proximal femoral fractures are prevalent injuries in the elderly, a growing population group in Brazil. The main related risk factors are osteoporosis, more prevalent in the female population, and advanced age. Methods: this is a retrospective, descriptive, exploratory and quantitative study, I seek to analyze the relevant and most prevalent points in this type of injury in the elderly, such as epidemiology, trauma mechanism and surgical approach, through the medical records of 69 patients over 60 years old. of age who suffered this fracture. Objective: to identify and quantify possible correlations found in elderly patients with proximal femoral fractures. Results: the patients in the analyzed sample had a mean age of 79.2 years, 75.3% were female, with a ratio of 3:1 females to every male. Low-energy trauma represented 97% of the etiology of fractures, with 71.7% of transtrochanteric fractures, 21.7% of femoral neck fractures and 8.6% of subtrochanteric fractures. Osteosynthesis was the method chosen for 82% of patients. The mean length of stay was 5.4 days and hospital mortality was 5.7%. Conclusion: the epidemiological profile of the patients was in agreement with the national literature. Male sex, chronic obstructive pulmonary disease and chronic renal failure were significant risk factors for in-hospital mortality. Osteoporosis reported by patients was similar to other national studies and lower than parameters demonstrated in radiography. Most of the patients analyzed had multiple risk factors for falling from standing height.